SOLVENT INFLUENCE ON THE STABILITY AND PROPERTIES OF Si4H4 ISOMERS BY COMPUTATIONAL METHODS - Nilchi,Masoomeh (Sociedad Chilena de Química, 2019)
ABSTRACT In this investigation, we was explored solvent influence on the stability and properties of different isomers of Si4H4 molecule in both gas and solution phases. Our calculation was performed at the M062X/Def2-TZVPP level of theory. For solution phase calculations, self-consistent reaction field (SCRF) approach was used by the polarizable continuum model (PCM). The solvation model applied the radii and non-electrostatic terms of the solvent model density (SMD). The eight selected solvents were Chloroform, o-NitroToluene, CycloHexanone, TetraHydroFuran, n,n-DiMethylFormamide, DiMethylDiSulfide, PropanoNitrile and DiChloroEthane. The stability of the isomers were investigated in both phases and the solvation energy values of them were calculated. Solvent effect on the frontier orbital energy and HOMO-LUMO gap was clarified. The most instance vibration of the most stable isomer was determined and solvent influence on the wavenumber of this vibration was explored. Lastly, natural bond analysis (NBO) was used for the illustration of the Si-Si chemical bonds, strongest interaction and natural atomic charges of the most stable isomer.